2013
DOI: 10.1111/gwat.12045
|View full text |Cite
|
Sign up to set email alerts
|

An Unsteady State Tracer Method for Characterizing Fractures in Bedrock Wells

Abstract: Evaluating contaminants impacting wells in fractured crystalline rock requires knowledge of the individual fractures contributing water. This typically involves using a sequence of tools including downhole geophysics, flow meters, and straddle packers. In conjunction with each other these methods are expensive, time consuming, and can be logistically difficult to implement. This study demonstrates an unsteady state tracer method as a cost-effective alternative for gathering fracture information in wells. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Their high cost per well is a significant disincentive for conducting needed detailed characterization. Brainerd and Robbins () and more recently Libby () have attempted to develop simplified and less costly single‐well tracer methods for characterizing fracture hydraulic properties and water quality. Brainerd and Robbins () developed a steady‐state tracer method to identify fractures and determine their hydraulic heads and transmissivities.…”
Section: Introductionmentioning
confidence: 99%
“…Their high cost per well is a significant disincentive for conducting needed detailed characterization. Brainerd and Robbins () and more recently Libby () have attempted to develop simplified and less costly single‐well tracer methods for characterizing fracture hydraulic properties and water quality. Brainerd and Robbins () developed a steady‐state tracer method to identify fractures and determine their hydraulic heads and transmissivities.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that while formation DO concentrations certainly play a role in the resulting well screen concentrations, the effects of flow are the primary factor controlling changes in DO concentrations. Chlebica and Robbins ( 2013 ) showed that the DO profiles were comparable to conservative rhodamine profiles by Libby and Robbins ( 2012 ), demonstrating that given the timeframe of testing, changes in DO concentrations are more a function of flow conditions than abiotic or biotic reactions. Flow conditions derived from the DO alteration method have been found to be consistent with independent measures of flow in wells (heat pulse flow meter measurements by Chlebica and Robbins [ 2013 ] and here with respect to multilevel sampling data).…”
Section: Potential Controls On Do Concentrationsmentioning
confidence: 85%
“…Flow conditions in the wells have been characterized using geophysical and tracer dilution methods (Chlebica and Robbins, 2013; Libby and Robbins, 2014). Geophysical characterization has included caliper, optical televiewer, acoustic televiewer, and heat‐pulse flow meter logging (Cagle, 2005).…”
Section: Methodsmentioning
confidence: 99%